Faecal biomarker patterns in patients with symptoms of irritable bowel syndrome. Issue 4 (7th March 2016) - Emmanuel, Anton; Landis, Darryl; Peucker, Mark; Hungin, A Pali S
Abstract : Objective: To determine rates of faecal biomarker results capable of suggesting potentially treatable causes of irritable bowel syndrome (IBS) symptomatology in a population of patients with symptoms of IBS who meet Rome III criteria for that condition. Design: Descriptive, retrospective study in which faecal biomarker results (dichotomised into 'normal' and 'abnormal' values) were related to data from patient-completed questionnaire data identifying demographics, Rome III criteria for IBS and IBS phenotype (IBS-D, IBS-C, IBS-M and IBS-U). Setting: Commercial reference laboratory. Patients: Individuals whose physicians ordered faecal biomarker testing for evaluation of chronic abdominal symptoms consistent with IBS. Interventions: None. Main outcome measures: Rates of occurrence of abnormal results on any of seven faecal biomarkers suggesting a treatable cause for IBS symptoms. Results: Abdominal symptoms meeting Rome III criteria for IBS were present in 3553 records (the population), which were subjected to further analysis. Abnormal biomarker results (the outcomes) occurred in 94% of cases; 73% and 65% of records indicated growth of a bacterial potential pathogen and low growth of beneficial organisms, respectively. Abnormal results for all other faecal biomarkers occurred with frequencies from 5% to 13%. Frequency of abnormal results for elastase, calprotectin, eosinophil protein X, and beneficial organisms rose significantly with age, and differed significantly across IBS phenotypes. Conclusions: A large proportion of patients manifesting symptoms meeting Rome III IBS diagnostic criteria have faecal biomarker results indicating potential underlying, treatable causes of their symptoms. Faecal biomarker testing is an appropriate means of identifying potentially treatable causes of IBS symptoms.